Non-Semisimple Lie Algebras of Block Matrices and Applications to Bi-Integrable Couplings (Advances in Applied Mathematics and Mechanics, 2013)
We propose a class of non-semisimplematrix loop algebras consisting of3×3 block matrices,and form zero curvature equations from thepresented loop algebras to generate bi-integrable couplings. Applications are made for the AKNS soliton hierarchy andHamiltonian structures of the resulting integrable couplingsare constructed by using the associated variationalidentities.